2014
DOI: 10.1016/j.rmcr.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pneumothorax in a teenager with prior congenital pulmonary airway malformation

Abstract: Congenital pulmonary airway malformation (CPAM), previously referred to as congenital cystic adenomatoid malformation (CCAM), is a developmental malformation of the lower respiratory tract and the most commonly reported congenital lung lesion. Affected patients typically present with respiratory distress in the neonatal period from expanding cysts and resulting compression of surrounding lung parenchyma. However, some patients also remain asymptomatic until later in life. In this report, we present a case of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Another important consideration concerns other congenital defects that could be associated with CCAM, for instance, bilateral renal agenesis, hydrocephalus, gastrointestinal or abdominal wall defects (diaphragmatic hernia, jejunal atresia, and tracheoesophageal fistula), spinal deformities (cervical spine/thoracic spine), epiaortic vessels and myocardial anomalies (truncus arteriosus and tetralogy of Fallot), and sirenomelia [ 40 ]. Patients with CCAM may present with clinical features of pneumothorax in the early neonatal period [ 41 , 42 ]. Huang et al reported that different factors are independently associated with a poor outcome; for example, gestational age at birth, birthweight, Apgar score, and the diagnosis time could be considered fundamental to the survival rate [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another important consideration concerns other congenital defects that could be associated with CCAM, for instance, bilateral renal agenesis, hydrocephalus, gastrointestinal or abdominal wall defects (diaphragmatic hernia, jejunal atresia, and tracheoesophageal fistula), spinal deformities (cervical spine/thoracic spine), epiaortic vessels and myocardial anomalies (truncus arteriosus and tetralogy of Fallot), and sirenomelia [ 40 ]. Patients with CCAM may present with clinical features of pneumothorax in the early neonatal period [ 41 , 42 ]. Huang et al reported that different factors are independently associated with a poor outcome; for example, gestational age at birth, birthweight, Apgar score, and the diagnosis time could be considered fundamental to the survival rate [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…CPAM can manifest in various ways, with respiratory distress being the most common clinical presentation in neonates, regardless of which type of CPAM the neonate has. In about 50 % of affected newborns, CPAM can remain clinically silent until later in life; then, it could manifest as hemoptysis, dyspnea, chest pain, and cough, or it could be discovered coincidentally during imaging for a different reason or while investigating the etiology behind recurrent respiratory infections; spontaneous pneumothorax could also occur with CPAM [ 9 , 12 ]. In our case, the patient had cough, pneumothorax, dyspnea, and chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is considered the treatment of choice for CPAM to confirm the diagnosis and avoid the high potential of pulmonary infection and turning into malignancy [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 Adult patients with undiagnosed CPAMs can present with recurrent pneumonia, pneumothorax, bullae, haemoptysis or dyspnoea. 7,9,10 The differential diagnosis in adults includes acquired cystic lesions (i.e. pulmonary tuberculosis [TB]) or congenital lesions (i.e.…”
Section: Discussionmentioning
confidence: 99%